UPAYA MITIGASI RISIKO PEMBIAYAAN MURABAHAH PADA KSPPS BMT AMANAH UMMAH SURABAYA - Elicha Pusparini; Muhammad Nafik Hadi Ryandono (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
Sharia Cooperation as a micro financial institution does its function to collect and distribute money. Sharia cooperation, as how it works, is initiated by its members, for the members, and from the members. Therefore, the fund channeling done by sharia cooperation is only focusing to the members’ welfare. On doing the business, BMT utilizes Sharia contracts such as mudharabah, musyarakah, murabahah, and many more. BMT which was established based on cooperation basic law, must follow the provisions from Ministry of Cooperation in carrying out the business activities.This study uses a qualitative approach with a case study method. The results of this study are risk control measures in murabahah financing contained in the Standard Operating Procedure (SOP). The form of risk control is directed at risk mitigation actions, if risk mitigation is less accurate it will lead to problematic financing. To reduce the number of problematic financing is carried out with preventive measures when submitting, analyzing, realizing and paying off. By focusing on these stages, the possibility of a risk can be minimized.Keywords: Risk, Financing Risk, Murabahah Agreement, Sharia Cooperative, BMTREFFERENCESAfifudin dan Beni Ahmad Saebani. 2012. Metodelogi Penelitian Kualitatif. Bandung:Pustaka SetiaAhmadiono. 2014. Mengendalikan Risiko Lembaga Keuangan Mikro Syariah. Jember:Al-Mashraf, Vol.1, No.  01 OktoberAjija, S. Rohmatul, dkk. 2018. Koperasi BMT Teori, Aplikasi dan Inovasi. Karanganyar.CV. Inti Media KomunikaAl-Hasan, Fahadil Amin. 2018. Analisis pelaksanaan Akad Murabahah di LembagaKeuangan Syariah (BMT)Antonio. M. Syafii. 2001. Bank Syariah dari Teori ke Praktek. Jakarta: Gema InsaniPressDjojosoedarso, Soeisno. 1999. Prinsip-prinsip manajemne risiko dan asuransi. Jakarta.Salemba EmpatBi.go.id diakses pada 18 November 2018 pukul 20.22 Tentang Undang-UndangNomor 20Tahun 2008Cokrohadisumarto, Widiyanto bin Mislan, dkk.2016. BMT: Praktik dan kasus. Jakarta.Rajawali Pers.Fikruddin, Tahta. 2015. Strategi Penanganan Risiko Pembiayaan Murabahah padaBMT Se-Kabupaten Demak. Kudus. Equilibrium 3(2) 254-270Hendrojogi. 2004. Koperasi Asas-Asas, Teori dan Praktik. Jakarta: PT. RajaGrafindoPersadaKarim, Adiwarman Azwar. 2010. Bank Islam: Analisis Fiqih dan Keuangan. Jakarta: PT.RajaGrafindo PersadaKusmiyati, A. N. S. 2007. Risiko Akad dalam pembiayaan Murabahah pada BMT diYogyakarta (dari Teori ke Terapan). Yogyakarta. La_Riba Jurnal EkonomiIslam Vol 1 (1)27-41Lubis, Suhrawardi K. Dan Farid Wajdi. 2012. Hukum Ekonomi Islam. Jakarta. SinarGrafikaMuhamad. 2016. Manajemen Keuangan Syariah Analisis fiqh danKeuangan.Yogyakarta. UPPSTIM YKPNNawawi, Ismail. 2009. Ekonomi Kelembagaan Syariah: Dalam Pusaran EkonomiGlobalSebuahTuntutan dan Realitas. Surabaya. CV. Putra Medika Nusantara.Rivai, Veithzal dan Andria Permata Veithzal. 2008. Islamic Financial Management:Teori, Konsepdan Aplikasi Panduan Praktis untuk Lembaga Keuangan,Nasabah, Praktisi danMahasiswa. Jakarta: Raja Grafindo PersadaRivai, Veithzal dan Rifki Ismal. 2013. Ismalic Risk Management Fot Islamic Bank.Jakarta: Gramedia Pustaka Utama.Romdhoni, A. H. 2016. Analisis Komparasi Manajemen Risiko pada KoperasiSyariah diKabupaten Boyolali. Surakarta. Jurnal Ilmiah Ekonomi Islam Vol.02 (03) 1-15Suyanto, Bagong dan Sutinah. 2008. Metode Penelitian Sosial: Berbagai PendekatanAlternatif. Jakarta. KencanaYusuf, Saifullah. 2017. Perubahan Berkelanjutan: Gotong Royong MemakmurkanJawa Timur.Surabaya. Airlangga university press.Yin, R. K. 2009. Studi Kasus: Desain dan Metode. Jakarta. Raja Wali